Design of a multi-layer interior ferrite permanent magnet synchronous machine for traction applications - Xia, Bing; Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Wu, D (Institution of Engineering and Technology (IET), 2014)
A novel design of interior ferrite permanent magnet synchronous machine with multi-layer configuration is proposed for traction applications. Although the ferrite magnet can be disadvantaged by its low residual flux density and energy product, it is proposed that flux-focusing and multi-layer configurations can be utilized to harness both permanent magnet (PM) torque and reluctance torque to recoup the loss of the PM torque due to its intrinsic property. The machines with up to three-layer magnets are presented and evaluated comprehensively. The results suggest that the two-layer machine provides the best performance among the three configurations. Furthermore, compared against a commercial rare-earth equivalent, the proposed ferrite machine is shown to have nearly the same torque with 32% less electromagnetic losses. The findings underpin interior ferrite permanent magnet synchronous machine as an attractive alternative for traction applications
Keywords: Ferrite magnet; flux-focusing; interior permanent magnet; traction motor.